Tinjauan Hukum Perjanjian Gadai Lahan Sawah Dengan Dua Pihak Pemegang Gadai di Kabupaten Wajo - Sulaeman; Putri Rahmadani; Maulid, Arba Juliana; Nur Awalia; Ramadhani, Nurhidayah; Nurfadillah, Putri Annisa; Gau, Andi Tenri; Mildayanti (Legal Journal of Law, 2024)
The purpose of this study was to determine the implementation of a rice field mortgage agreement with two pawnholders and to determine the resolution of disputes due to the existence of two pawnholders in a rice field mortgage agreement. This study was conducted in Liu Village, Sabbangparu District, Wajo Regency using data collection methods through direct observation and interviews with the community. The data and information obtained by the author were analyzed qualitatively and then described descriptively so that the author could obtain answers to the problems studied. Based on the results of the study, it can be concluded that economic factors are one of the factors causing the occurrence of rice field mortgage agreements, and the lack of legal literacy in the community has led to the implementation of rice field mortgage agreement practices using the principle of kinship (oral agreements) and the form of settlement of default disputes in rice field mortgage agreements in Liu Village is settlement through non-litigation, namely by consensus.